Determination of a serum total calcium concentration threshold for accurate prediction of ionized hypercalcemia in dogs with and without hyperphosphatemia. (6th November 2019) - Groth, Elizabeth M.; Chew, Dennis J.; Lulich, Jody P.; Tommet, Megan; Rendahl, Aaron K.; Husbands, Brian D.; Furrow, Eva
Abstract: Background: Total serum calcium (tCa) concentrations are poorly predictive of ionized calcium (iCa) status in dogs. Hypothesis: There is an optimal threshold of tCa concentration that is highly predictive of ionized hypercalcemia and this threshold is higher in hyperphosphatemic dogs as compared to nonhyperphosphatemic dogs. Animals: Nonhyperphosphatemic (n = 1593) and hyperphosphatemic (n = 250) adult dogs. Methods: Retrospective medical record review of paired tCa and iCa concentration measurements in dogs presented to a university teaching hospital over a 5‐year period. Positive and negative predictive values, sensitivity, and specificity were calculated for tCa concentration thresholds of 11.0‐15.0 mg/dL (upper limit of laboratory reference interval = 11.5 mg/dL) in nonhyperphosphatemic and hyperphosphatemic groups. Results: In nonhyperphosphatemic dogs, an optimal tCa concentration threshold of 12.0 mg/dL resulted in a positive predictive value of 93% (95% confidence interval [CI], 84%‐98%) and sensitivity of 52% (95% CI, 43%‐61%) for ionized hypercalcemia. An optimal tCa concentration threshold was not identified for hyperphosphatemic dogs. The nonhyperphosphatemic dogs had a higher prevalence of ionized hypercalcemia than the hyperphosphatemic dogs (7 versus 3%, P = .04) and a lower prevalence of ionized hypocalcemia (23 versus 62%, respectively; P  < .001). Conclusions and Clinical Importance: High tCa concentrations are strongly predictive of ionized hypercalcemia in nonhyperphosphatemic adult dogs and should prompt further diagnostic testing to determine the underlying cause of hypercalcemia. In this population, dogs without increased tCa concentrations rarely had ionized hypercalcemia, but iCa concentrations still should be evaluated in patients with tCa concentrations within the reference interval if there is clinical suspicion for calcium abnormalities.